Strategies of the Indonesian Embassy in Kuala Lumpur in Resolving Education Problems for Undocumented Children of Indonesian Migrant Workers in Malaysia - Agustina, Namira; Azizah, Nur (research, training and philanthropy institution Natural Aceh, 2024)
This article aims to highlight the strategies used by the Indonesian Embassy in Kuala Lumpur to address the educational challenges faced by the children of undocumented Indonesian migrant workers in Malaysia. The research focus on the concept of national interest also aims to provide further understanding of how diplomacy and foreign policy can be used to protect children's rights and improve their access to education. The research methodology used is a descriptive qualitative method, focusing on the concept of national interest to answer the research questions posed in this journal article. The research findings reveal that the Indonesian Embassy in Kuala Lumpur has implemented several strategies to address the educational challenges for children of undocumented Indonesian migrant workers in Malaysia. The findings may encourage cooperation between countries to exchange information and best practices in addressing similar education issues at the international level. In addition, the focus on the concept of national interest shows the potential to integrate education aspects in foreign policy plans to ensure the protection of national interests. This includes the establishment of guidance and assistance centers in the registration process to obtain the National Student Identification Number (NISN). The ethical implications of this research include attention to children's right to education, especially children in vulnerable situations. The results can also serve as a basis for further research, by evaluating the effectiveness of the strategies that have been implemented and identifying other areas that require further attention.